A study of the effect of yoga on C-reactive protein, lipid profile and insulin resistance in obese patients - Gupta, Anirudh; Tayal, Nishant; Chaudhary, Manu; Arya, Tungvir Singh; Agarwal, Vidushi (International Journal of Advances in Medicine, 2022)
Background: Obesity is defined as a state of excess adipose tissue mass. In the last decade, there has been an alarming prevalence of obesity in the developed and developing countries like India. While modern medicine has so far been unable to control the menace of obesity, yoga offers an alternative holistic approach to tackle the problem of obesity by inculcating an approach towards balanced diet (Satwik aahar), physical activity and behavior modification (through pranayama). In this study, we have included the core anthropometric parameters of obesity, as well as associated abnormalities secondary to obesity like, insulin resistance, glucose intolerance, hypertension, atherogenic dyslipidemia. Methods: The study was conducted in the department of medicine, L. L. R. M. Medical College and associated S. V. B. P. Hospital, Meerut, U.P. during 2020-2021 with the objective to assess the role of yoga therapy in modifying anthropometric and biochemical parameters of obese patients. It was a prospective, controlled trial in which 120 obese patients (BMI≥25 kg/m2) were enrolled and followed for a period of six months. Results: Yoga therapy along with dietary restrictions is highly effective in improving the various anthropometric and biochemical parameters in obese patients and also beneficial in controlling complications like hypertension, diabetes and dyslipidemias secondary to obesity. It also improved the quality of life of these patients. Conclusions: This study is a modest attempt to ascertain the role of yoga in obesity and it hopes to encourage further research in the field.